2019
DOI: 10.1111/nyas.14020
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and disadvantages of apoptosis in the aging process

Abstract: Researchers cannot predict as yet how long a human being can live. Life expectancy has been steadily increasing in the last century, but perhaps not always the quality of life in parallel with it. Future generations will be faced with the problems of an increased life expectancy along with the emergence of new age-related diseases. A deeper understanding of the aging process is crucial to ameliorate, if not to prevent, these projected new old-age diseases. One of the mechanisms responsible for healthy aging is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Argüelles and colleagues propose that efficient apoptosis could be considered a pleiotropic aging factor, positive during development but negative during adulthood (Argüelles et al 2019). We suggest that the same logic applies to senescence: enhanced senescence may be a positive feature during development although accumulation of senescent cells in adulthood remains pro aging.…”
Section: Longevity Is Positively Associated With Stress Induced Senescencementioning
confidence: 66%
“…Argüelles and colleagues propose that efficient apoptosis could be considered a pleiotropic aging factor, positive during development but negative during adulthood (Argüelles et al 2019). We suggest that the same logic applies to senescence: enhanced senescence may be a positive feature during development although accumulation of senescent cells in adulthood remains pro aging.…”
Section: Longevity Is Positively Associated With Stress Induced Senescencementioning
confidence: 66%
“…Apoptosis is the process of programmed cell death, which is considered as a vital component of cell life including normal cell turnover, proper development, and functioning of the immune system, hormone-dependent atrophy et al [20,21]. Numerous studies have recently reported that inappropriate apoptosis (either too little or too much) is a factor involved in various diseases including neurodegenerative diseases, CVD, and cancer [22][23][24][25].…”
Section: Apoptosismentioning
confidence: 99%
“…In other words, age-related factors could predispose old individuals to develop this common neurodegenerative disease. Impaired mitochondrial functions [1,5], the cell apoptosis [6,7], and the chronic inflammatory process [8] showed commonalities in both PD and normal aged people. Third, the loss of substantia nigra (SN) neurons between normal aging and PD was significant, where the loss of neurons was 28.3% in older controls compared with younger controls, and the loss of pigmented neurons in PD was 73% compared with older controls [9].…”
Section: Introductionmentioning
confidence: 99%